Pterostilbene fluorescent probes as potential tools for targeting neurodegeneration in biological applications - Lidia Ciccone; Susanna Nencetti; Maria Marino; Chiara Battocchio; Giovanna Iucci; Iole Venditti; Martina Marsotto; Emiliano Montalesi; Simone Socci; Beatrice Bargagna; Elisabetta Orlandini (Journal of Enzyme Inhibition and Medicinal Chemistry)
Several epidemiological studies suggest that a diet rich in fruit and vegetables reduces the incidence of neurodegenerative diseases. Resveratrol (Res) and its dimethylated metabolite, pterostibene (Ptb), have been largely studied for their neuroprotective action. The clinical use of Res is limited because of its rapid metabolism and its poor bioavailability. Ptb with two methoxy groups and one hydroxyl group has a good membrane permeability, metabolic stability and higher in vivo bioavailability in comparison with Res. The metabolism and pharmacokinetics of Ptb are still sparse, probably due to the lack of tools that allow following the Ptb destiny both in living cells and in vivo. In this contest, we propose two Ptb fluorescent derivatives where Ptb has been functionalised by benzofurazan and rhodamine-B-isothiocyanate, compounds 1 and 2, respectively. Here, we report the synthesis, the optical and structural characterisation of 1 and 2, and, their putative cytotoxicity in two different cell lines.